Utilising building information modelling (BIM) for implementation of sustainable resort development in Maldives - Ahmed Tholhath,; Ibrahim, Rahinah (Faculty of Design & Architecture, Universiti Putra Malaysia, 2013)
Ineffective collaboration within project participants during building process is causing poor implementation co-ordination for sustainable development of resort projects in the Maldives. Attainment of acceptable level of quality in the construction industry has long been a problem. Utilisation of (Building Information Modelling) BIM for implementation co-ordination during building process in Maldives and the implications on two selected projects was studied. The conditions (planning errors, design errors, amendments due to design errors, misinterpretation of drawings, use of 3D models, discontinuation of information, construction practicality, onsite errors, use of prefabrication, amendments due to construction errors and time extensions) identified from the projects were related to its phenomenon of the study to increase quality and productivity while decreasing cost and duration. BIM will improve implementation co-ordination by increasing construction productivity and prefabrication with less rework on site. Innovation in planning and implementation will contribute to make Maldives build a sustainable, eco-friendly construction industry. Effective collaboration will improve implementation co-ordination and integration through BIM during building process with innovative planning in the Maldives, hence improve construction industry and develop sustainable resort projects.